PENGEMBANGAN KURIKULUM DI SD ISLAM AL AZHAR 38 BANTUL YOGYAKARTA - Anggitiyas Sekarinasih (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
Abstract: Curriculum is a set of plans and arrangements that contain objectives, content, and lesson materials and used as guidelines for the implementation of learning activities so that the learning process can run smoothly. The current 2013 curriculum is defined as a national curriculum, which means all schools are required to use it. However, schools are allowed to develop the curriculum to suit their needs. SDI Al Azhar 38 Bantul is one of the primary schools in Yogyakarta that has developed a curriculum in its education. Al Azhar School uses a mixed curriculum of the national curriculum and curriculum from Al Azhar Central Foundation which is then supplemented with a curriculum of development from school and local potential. Curriculum of Al Azhar is called the Kurikulum Pengembangan Pribadi Muslim (KPPM). KPPM curriculum aims to hone akhlakul karimah in students. In addition Al Azhar 38 Bantul also has a curriculum Education Al Qur'an is an additional curriculum to optimize the ability of children in reading the Qur'an. This curriculum consists of reading material of the Qur'an and recitation juz 30. Keywords: Curriculum Development, Al Azhar